Endometrial stromal cell inflammatory phenotype during severe ovarian endometriosis as a cause of endometriosis-associated infertility. Issue 4 (October 2020) - Anupa, Geethadevi; Poorasamy, Jeevitha; Bhat, Muzaffer A.; Sharma, Jai Bhagwan; Sengupta, Jayasree; Ghosh, Debabrata
Abstract: Research question: Do endometrial stromal cells from primary infertile patients with severe ovarian endometriosis display differential secretory profiles of inflammation-associated cytokines during the implantation window that may cause infertility? Design: Forty-eight cytokines were measured in conditioned medium of isolated endometrial stromal cells obtained from primary infertile patients without endometriosis (control group, n  = 12) or with stage IV ovarian endometriosis (ovarian endometriosis group, n  = 14) using multiplex assays. Key cytokines showing differential secretory profiles were validated using Western immunoblotting. Cellular phenotypic validation was carried out in vitro by comparing proliferation and migration capacity between control ( n  = 6) and ovarian endometriosis ( n  = 7) groups. Results: CCL3, CCL4, CCL5, CXCL10, FGF2, IFNG, IL1RN, IL5, TNFA, and VEGF could be detected only in the conditioned media of stromal cells obtained from the ovarian endometriosis group. Among other cytokines detected in the conditioned media of both groups, CCL2 ( P  = 0.0018), CSF3 ( P  = 0.0017), IL1B ( P  = 0.0066), IL4 ( P  = 0.036), IL6 ( P  = 0.0039) and IL13 ( P  = 0.036) were found to be higher, whereas the concentration of IL18 was lower ( P  = 0.023) in the ovarian endometriosis group. Concentrations of CCL2, IL1B, IL4 and IL13 in conditioned medium reflected significant diagnostic performance for predicting ovarian endometriosis. Cellular phenotypic validation in vitro revealed an enhanced proliferative phenotype ( P  = 0.046) with no change in cell migratory capacity of endometrial stromal cells from the ovarian endometriosis group. Conclusions: Endometrial stromal cells derived from severe ovarian endometriosis samples displayed a hyperinflammatory and hyperproliferative bias in the endometrial stroma during the 'window of implantation' putatively causing loss of fecundability.